How do we define „WORKER” in the European Union - Pop Mihaela (EIRP Proceedings, 2012)
The citizens who exercise their right of free movement are protected by the dispositions ofEuropean Union regarding coordination of social security. A person can travel between countries fromEuropean Union in order to search for a job, according his qualification and his studies. Free movement is ameans of creating a European employment market and of establishing a more flexible and more efficientlabor market, to the benefit of workers, employers and Member States. It is common ground that labormobility allows individuals to improve their job prospects and allows employers to recruit the people theyneed. It is an important element in achieving efficient labor markets and a high level of employment. We cansay that Romania is a country of migrants. According to official government estimates are about 3 millionRomanian workers in EU countries. I followed that this article to ensure an efficient and accurate informationon the term "worker" and the possibilities for labor migration in EU countries in accordance with theprinciple of freedom of movement. A novelty of this article is represented by comment on variousapproaches, nuances and connotations that were associated with the concept of "worker" by different authors.